COVID-19 and health passport - Kosmadakis, Nikos; Lapidis, Konstantinos (HAPSc Policy Briefs Series, 2020)
The health crisis in Europe brought about a series of changes to the daily lives of millions of people in recent months. It is a crisis which will have its material mark on the social, economic life not only in Europe, but also worldwide. The consequences will be incalculable if an effective drug or vaccine will not be found in time. Many European economies will collapse, and tourism will suffer. Taking the importance of tourism in many European countries into account, we have compiled the following text focusing on the health passport or protocol. It is a policy that many European countries will follow. The defense of Public Health goes beyond the individual Good, while the economy takes second place. Through this analysis, we try to capture the challenge of health ethics. The health protocol forms a new kind of Ethics which abandons its previously ethical character, while obtains utilitarian characteristics. At the same time, the public debate as it takes place in Europe is clearly mentioned and it is also proposed the Health Passport as kind of policy. The health passport should be aligned with the strengthening of European institutions and procedures.